2015
DOI: 10.1021/acs.jpcc.5b09861
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Intrusion–Extrusion of Water and Electrolyte Solutions in Pure-Silica LTA Zeolite

Abstract: The energy performances of pure-silica LTA-type zeosil were studied by intrusion–extrusion of water and concentrated aqueous solutions of LiCl. The LTA structure is characterized by a highly symmetrical three-dimensional pore system that consists of large cages separated by eight-membered-ring openings. The LTA-type zeosil–water system exhibits a bumper behavior with an intrusion pressure of 20 MPa and an absorption energy of 3.4 J g–1. Despite the small pore openings (0.41 × 0.41 nm2), the value of the intrus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 35 publications
7
53
0
Order By: Relevance
“…An important number of other all-silica zeolites (zeosil) was investigated by the Patarin group over the years, from 2001 until very recently. [40][41][42][43][44][45][46][47][48][49][50] They are gathered in Table 1, together with the main intrusion-extrusion properties. As already mentioned the energy storage behavior can either be depicted as a ''spring'' (S) when the intrusion-extrusion cycle is fully reversible, a ''shock absorber'' (SA) when the cycle displays an hysteresis, or a ''bumper'' (B), when the cycle is incomplete and some water is retained in the porous framework upon pressure release.…”
Section: Other Zeosil-water Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…An important number of other all-silica zeolites (zeosil) was investigated by the Patarin group over the years, from 2001 until very recently. [40][41][42][43][44][45][46][47][48][49][50] They are gathered in Table 1, together with the main intrusion-extrusion properties. As already mentioned the energy storage behavior can either be depicted as a ''spring'' (S) when the intrusion-extrusion cycle is fully reversible, a ''shock absorber'' (SA) when the cycle displays an hysteresis, or a ''bumper'' (B), when the cycle is incomplete and some water is retained in the porous framework upon pressure release.…”
Section: Other Zeosil-water Systemsmentioning
confidence: 99%
“…The same phenomenon was observed in the case of BEC zeosil-LiCl aqueous solution systems, 46 and to a certain extend to LTA zeosil. 48 In the case of CHA zeosil, the mixed shockabsorber-bumper behavior 40 turned into a pure shock-absorber behavior in presence of aqueous LiCl solutions. 87 Along these lines, it was also shown that weakly hydrophilic materials such as high Si/Al ratio zeolites 88 or COK-14 zeolites 89 could exhibit an intrusion transition in the presence of electrolyte aqueous solutions.…”
Section: Intrusion Of Electrolyte Solutionsmentioning
confidence: 99%
“…The intrusion of highly concentrated electrolyte solutions can also change the behavior of the "zeosil-aqueous solution" system. It was the case, for instance, for the LTA-and *BEA-type zeosil [27,19].…”
Section: Introductionmentioning
confidence: 98%
“…Water intrusion-extrusion capacity [mm 2 g À1 ] PSS-2 1000 Pure silicaITQ-7 [46] 210 Pure silicaL TA [48] 170 Pure silicaBEA [52] 140 IFR [51] 136 MTW [50] 114 AFR [53] 390 AEI [53] 370 ZIF-8 [54,55] up to 480 MIL-100 [55] up to 820 Cr-MIL-101 [55] up to 1400 UiO-66 [55] up to 400 CPO-27 [55] up to 680 MCM-41 [56] up to 400 tively low pressures (intrusion pressure up to 5MPa with an extrusionp ressure of 0.3MPa). The material was able to take up as ubstantial amount of liquid (1000 mm 3 g À1 for water and between 1100-1200 mm 3 g À1 for LiCl solution) in the pores.…”
Section: Methodsmentioning
confidence: 99%